Difference between revisions of "Sums and Perfect Sqares"
(Propose for deletion) |
|||
Line 1: | Line 1: | ||
− | Here are many proofs for the | + | Here are many proofs for the theorem that <math>1+2+3+...+n+1+2+3...+(n-1)=n^2</math> |
− | PROOF 1 | + | ==PROOF 1== |
+ | <math>1+2+3+...+n+1+2+3...+(n-1)=n^2</math>, Hence <math>\frac{n(n+1)}{2}+\frac{n(n+1)}{2}=n^2</math>. If you dont get that go to words''.Conbine the fractions you get <math>\frac{n(n+1)+n(n-1)}{2}</math>. Then Multiply: <math>\frac{n^2+n+n^2-n}{2}</math>. Finnaly the <math>n</math>'s in the numorator cancel leaving us with <math>\frac{n^2+n^2}{2}=n^2</math>. I think you can finish the proof from there. | ||
+ | ==PROOF 2== | ||
+ | The <math>1+2+\cdots+n</math> part refers to an <math>n</math> by <math>n</math> square cut by its diagonal and includes all the squares on the diagonal. The <math>1+2+\cdots+ n-1</math> part refers to an <math>n</math> by <math>n</math> square cut by its diagonal but doesn't include the squares on the diagonal. Putting these together gives us a <math>n</math> by <math>n</math> square. | ||
− | PROOF | + | ==PROOF 3== |
+ | We proceed using induction. If <math>n = 1</math>, then we have <math>1+0=1^2</math>. Now assume that <math>n</math> works. We prove that <math>n+1</math> works. We add a <math>2n+1</math> on both sides, such that the left side becomes <math>1+2+\cdots + (n+1)+1+2+\cdots + n = n^2 + 2n + 1 = (n+1)^2</math> and we are done with the third proof. | ||
− | + | {{delete|unrelated title, unnecessary page}} | |
− | |||
− | |||
− | |||
− | |||
− |
Latest revision as of 12:47, 19 February 2025
Here are many proofs for the theorem that
PROOF 1
, Hence
. If you dont get that go to words.Conbine the fractions you get
. Then Multiply:
. Finnaly the
's in the numorator cancel leaving us with
. I think you can finish the proof from there.
PROOF 2
The part refers to an
by
square cut by its diagonal and includes all the squares on the diagonal. The
part refers to an
by
square cut by its diagonal but doesn't include the squares on the diagonal. Putting these together gives us a
by
square.
PROOF 3
We proceed using induction. If , then we have
. Now assume that
works. We prove that
works. We add a
on both sides, such that the left side becomes
and we are done with the third proof.
This article has been proposed for deletion. The reason given is: unrelated title, unnecessary page.
Sysops: Before deleting this article, please check the article discussion pages and history. |